Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0083948
|View full text |Cite
|
Sign up to set email alerts
|

Does Attrition during Follow-Up of a Population Cohort Study Inevitably Lead to Biased Estimates of Health Status?

Abstract: Attrition is a potential source of bias in cohort studies. Although attrition may be inevitable in cohort studies of older people, there is little empirical evidence as to whether bias due to such attrition is also inevitable. Anonymised primary care data, routinely collected in clinical practice and independent of any cohort research study, represents an ideal unselected comparison dataset with which to compare primary care data from consenting responders to a cohort study. Our objective was to use this metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
(44 reference statements)
1
24
1
Order By: Relevance
“…First, longitudinal data are often incomplete or unbalanced because of loss to follow‐up. Previous studies reported that attrition in the longitudinal survey was more complicated than often assumed, and attrition may not inevitably indicate bias and limit the generalizability of longitudinal comparisons . We used mixed‐effect linear regression models, which provided appropriate techniques for managing such a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, longitudinal data are often incomplete or unbalanced because of loss to follow‐up. Previous studies reported that attrition in the longitudinal survey was more complicated than often assumed, and attrition may not inevitably indicate bias and limit the generalizability of longitudinal comparisons . We used mixed‐effect linear regression models, which provided appropriate techniques for managing such a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that attrition in the longitudinal survey was more complicated than often assumed, and attrition may not inevitably indicate bias and limit the generalizability of longitudinal comparisons. 46,47 We used mixed-effect linear regression models, which provided appropriate techniques for managing such a challenge. Mixed-effect linear regression models can account for unbalanced or incomplete data under the assumption that observations are missing at random.…”
Section: Discussionmentioning
confidence: 99%
“…In order to interpret follow-up results, bias must be analyzed, corrected, and taken into account in clinical interpretation (Guyatt, 2009). However, even high proportions of LTFU do not necessarily cause uncontrollable bias for endpoint measures of a trial (Lacey, Jordan & Croft, 2013; Gustavson et al, 2012), e.g., a high proportion of LTFU makes it unreliable to calculate prevalences but cause—consequence analyses are still possible (Martikainen et al, 2007). In follow-up studies and trials that last for decades, it is next to impossible to achieve attrition less than 20–40%.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of the potential effects of attrition in the NorStOP cohorts confirmed that there was little evidence that responders at follow-up points represented any further selection bias to that present at baseline. 79 …”
Section: Box 1 Interpretation Of Indicatorsmentioning
confidence: 99%